2003
DOI: 10.1046/j.0001-690x.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and outcome of antidepressant medication in a general population: a prescription database and medical record study, in Jämtland county, Sweden, 1995

Abstract: This study provides evidence that the main use of SSRIs in 1995 is the treatment of depression. The study implies that SSRIs have a more favourable outcome in "real life" than TCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
4
33
0
2
Order By: Relevance
“…This may have implications on recommended length of treatment period and also on expected therapeutic response, since bipolar disorder and major depression with psychotic symptoms might be recalcitrant to treatment. However, previous studies have reported that depression is the most common indication for antidepressants in outpatient care followed by anxiety/panic disorders [34,35]. Finally, the register is based on purchases, and there is no information regarding adherence, nor is there any information regarding other forms of medical and psychological treatments.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This may have implications on recommended length of treatment period and also on expected therapeutic response, since bipolar disorder and major depression with psychotic symptoms might be recalcitrant to treatment. However, previous studies have reported that depression is the most common indication for antidepressants in outpatient care followed by anxiety/panic disorders [34,35]. Finally, the register is based on purchases, and there is no information regarding adherence, nor is there any information regarding other forms of medical and psychological treatments.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, in the present study we found a link between WHI and antidepressant treatment among men before controlling for work characteristics. It should be kept in mind that antidepressants are sometimes prescribed for indications other than depressive disorders such as anxiety, pain, and sleeping problems (35)(36)(37), but could be an indicator of mental health problems, and that treatment-seeking behaviors may influence drug prescriptions. This may be a partial explanation of the effect observed among men on this indicator and not major depression.…”
Section: Magnusson Hanson Et Almentioning
confidence: 99%
“…However, although there was good 26 information on prescribed medications there was no associated clinical information on indication for 27 use and we have assumed that use was in accordance with the medication name. While these 28 medications are occasionally prescribed for other indications, most studies have found that the most 29 common indications for antidepressant or anxiolytic prescribing are depression and anxiety 30 (Gardarsdottir et al, 2009;Henriksson et al, 2003). The dataset does not capture private 31 prescriptions or those issued by psychiatrists which may result in an underestimation of the effect.…”
Section: Discussion 34mentioning
confidence: 99%
“…was constructed using four Census variables (Congdon, 1996) are depression and anxiety (Gardarsdottir et al, 2009;Henriksson et al, 2003). Prescription 42 information, including BNF category, was retrieved from the Enhanced Prescribing Database (EPD), 43…”
Section: Area Characteristics 40mentioning
confidence: 99%